Characterization of aromas of instant oolong tea and its counterparts treated with two crude enzymes from Aspergillus niger. Issue 2 (17th October 2017) - Zhang, Liangzhen; Ni, Hui; Zhu, Yanbing; Yang, Yuanfan; Li, Lijun; Jiang, Zedong; Zheng, Fu Ping; Chen, Feng
Abstract: Sensory evaluation, GC–MS and omission test were used to characterize aromas of noninstant Oolong tea (NIOT), original instant Oolong tea (OIOT) and its counterparts treated by two enzyme extracts from Aspergillus niger . The results showed that OIOT had stronger sweet, fruity, and roasted notes, but weaker grass and floral notes than NIOT. After treated by the crude enzymes extracted from the fermented broth from tea waste (TW) medium, the treated‐OIOT had an improved aroma similar to that of NIOT, due to the increases of 2‐pentyl‐furan and 3‐ cis‐ hexen‐1‐ol. In comparison, after the treatment of crude enzymes from wheat bran and orange peel (WBOP) medium, the treated‐OIOT showed significantly aroma difference from NIOT and OIOT, which was attributed to the increases of 3 ‐cis ‐hexen‐1‐ol, γ‐terpinene, and β‐ trans ‐farnesene. These results revealed that the original aroma of OIOT could be effectively modified and improved by the enzyme extracts, particularly by that from the TW medium. Practical applications: Tea is one of the most popular beverages all over the world. Instant tea is an important tea product that is processed from teas by extraction, concentration and drying. Instant tea is more convenient than teas for industrially producing tea foods such as tea beverage, tea break, and tea ice cream. However, the aroma profile of instant tea is always inferior to those of the original unprocessed noninstant teas, because the characteristic aroma of the original unprocessed tea could undergo significant changes during the preparation of instant tea. The present manuscript shows two enzyme extracts from Aspergillus niger could improve the aroma of instant Oolong tea, providing interesting information to promote the aroma of instant tea via enzymatic treatments, which may help to develop effective approaches to enhancing the quality of instant teas.